Exploitation of ICT for strategic education marketing in Malaysian Public Institutions of Higher Learning (MPIHL) - Khayon, Mohaiminah; Alias, Rose Alinda (2006)
The advances in information and communication technology (ICT) and the astounding developments brought about by the Internet have robustly transformed the marketing landscape and how marketers conduct business. ICT allow marketers to deploy customerization and technologicalship marketing in a financially prudent way of creating and sustaining relationship with customers. OECD (2004) report shows that ICT is having far reaching impacts on performance and the success of individual organizations, in particular when it is combined in investment in skills, organizational changes and innovations. This trend will continue and the transformation of any organization, be it public or private, will depend upon the exploitation of ICT (Goodridge and Clayton, 2004). Numerous researches that investigated various ICT usage, adoption, diffusion and utilization can be found in information systems (IS) and marketing literatures. However, review on past studies show that abundant research has been done on electronic data interchange (EDI), and only Internet and e-mail has been studies in details. Different ICT have been studied individually by different researchers. A study is hitherto need to be done to examine the absorption and exploitation of all adopted ICT together in an organization for the purpose of comprehensive marketing activities in particular and organizational transformation in general. Therefore, this study attempts to fill the gap by exploring the extent of ICT exploitation for strategic education marketing in organizations in developing country. The focus is on the Malaysian Public Institutions of Higher Learning (MPIHL) in relation with radical changes undertaken at the Ministry of Higher Education Malaysia (MOHE) level and the Malaysia Prime Minister emphasizes put forth in Rancangan Malaysia Ke 9.